Risk Evaluation Study of Zhoushan Section of Xin'ao LNG Export Submarine Pipeline Based on Kent Method - Longsheng CHENG; Decai YOU; Dan WANG; Fei XIE (Liaoning Shiyou Huagong Daxue xuebao, 2025)
Risk evaluation is the core work of pipeline integrity management and the prerequisite and foundation for realizing risk prevention management. Zhoushan submarine pipeline has harsh service conditions, difficult monitoring and maintenance, and serious consequences of accidents. In order to ensure the safe operation of the submarine pipeline. Integrating the service conditions and operational characteristics of the Zhoushan section of the Xinao LNG submarine pipeline, this study first identifies risk factors through systematic hazard analysis. Subsequently, the modified Kent methodology is applied to quantify relative risk values. According to the size of the relative risk value, the risky pipeline sections of this LNG pipeline system were graded. The results show that the relative risk value of the Zhoushan section of the submarine pipeline is predominantly within the 100~200 range, and the risk rating is at a low level. Meanwhile, risk management measures and recommendations for Zhoushan submarine pipeline are proposed. These strategies are aimed at promoting the realization of a risk⁃level⁃based management mechanism, thus providing scientific guidance and reference bases for the safe operation of submarine pipelines.